Sequestration of RNA by grass carp Ctenopharyngodon idella TIA1 is associated with its positive role in facilitating grass carp reovirus infection. Issue 2 (October 2015) - Song, Lang; Wang, Hao; Wang, Tu; Lu, Liqun
Abstract Previous report demonstrated that grass carp reovirus (GCRV) infection resulted in unlinking cellular stress granule formation from aggregation of grass carp Ctenopharyngodon idella TIA1 (CiTIA1). Here, we provided evidence to show that CiTIA1 bound to synthesized ssRNA and dsRNA in vitro. Both GST-pull down assay and RNA immunoprecipitation analysis confirmed the association between GCRV-specific RNA and GST-tagged CiTIA1 in C. idella kidney (CIK) cells. Furthermore, CiTIA1 was shown to protect dsRNA of virus-origin from degradation in CIK cells through Northern blot analysis. Finally, transient overexpression of CiTIA1 enhanced the replication efficiency of GCRV in CIK cells. Taken together, our results suggested that cellular CiTIA1 might facilitate GCRV replication through sequestrating and protecting viral RNA from degradation.